(untitled) (SAARC Journal of Agriculture, 2020)
Livestock, the dairy sector in particular, has traditionally contributed to the Nepalese economy and livelihoods even though vegetarian centered food habits predominate. Despite a long chain of observations, discussions, and interventions, this sector has not realized substantial improvement. An International Livestock Research Institute (ILRI) developed tool, Feed Assessment Tool (FEAST), has been deployed to precisely analyze the livestock feeding system in the Kapilvastu, Palpa and Arghakhachi districts of Nepal. A large proportion of the populations, especially the youth segment, have migrated, and as a result the area under agricultural production is ever decreasing. The typical crop production pattern does not reflect any dominance of fodder crops, which limits the availability of feed and posesa serious threat to the expansion of commercial dairy enterprises. Additional barriers to increased productivity include a limited supply of labor, competition for resources (i.e. labor, land) with rice production and the significant number of indigenous dairy animals in the national herd. Policy barriers that include unaffordable credit, limited access to inputs and inadequate government support further hinder potential growth of the dairy sector of this region. A dairy focused program to utilize the land and other resources to commercialize the dairy sector in order to tap the potential of this geography could be the only alternative to contribute toward meeting the national objective of making the country self-sufficient in milk and its products by 2020. SAARC J. Agri., 17(2): 253-266 (2019)